Accuracy of Actigraphy Compared to Concomitant Ambulatory Polysomnography in Narcolepsy and Other Sleep Disorders - Alakuijala, Anniina (Front Neurol, 2021)
Actigraphy provides longitudinal sleep data over multiple nights. It is a less expensive and less cumbersome method for measuring sleep than polysomnography. Studies assessing accuracy of actigraphy compared to ambulatory polysomnography in different sleep-disordered patients are rare. We aimed to compare the concordance between these methods in clinical setting. We included 290 clinical measurements of 281 sleep laboratory patients (mean age 37.9 years, 182 female). Concomitant ambulatory polysomnography and actigraphy were analyzed to determine the agreement in patients with obstructive sleep apnea, narcolepsy, periodic leg movement disorder, hypersomnia, other rarer sleep disorders, or no organic sleep disorder. Bland-Altman plots showed excellent accuracy, but poor precision in single night results between the two methods in the measurement of sleep time, sleep efficiency, and sleep latency. On average, actigraphy tended to overestimate sleep time by a negligible amount, −0.13 min, 95% confidence interval [−5.9, 5.6] min in the whole sample. Overestimation was largest, −12.8 [−25.1, −0.9] min, in patients with obstructive sleep apnea. By contrast, in patients with narcolepsy, actigraphy tended to underestimate sleep time by 24.3 [12.4, 36.1] min. As for sleep efficiency, actigraphy underestimated it by 0.18 [−0.99, 1.35] % and sleep latency by 11.0 [8.5, 13.6] min compared to polysomnography. We conclude that, in measuring sleep time, actigraphy is reasonably reliable and helpful to be used for a week or two to exclude insufficient sleep in patients with the suspicion of narcolepsy. However, the effectiveness of actigraphy in determining sleep seems to decrease in subjects with low sleep efficiencies.